Orisinalitas Pneumatologi John Calvin sebagai “Teolog Roh Kudus” - Herman Herman; Ceria Ceria; Fredy Simanjuntak (Sekolah Tinggi Teologi Real Batam, 2022)
John Calvin is one of the foremost theologians among reformed theologians. His works are a major contribution to the history of Protestant development even to the present day. But along the way, the development of Protestant theology has produced two views on the sustainability of the gifts of the Spirit. One of the views is to see that the gifts of the Holy Spirit no longer occur after the Biblical canonization (cessationism). This view is dominated by most Calvinist theologians and eventually creates the stigma that Calvin theology does not emphasize the Holy Spirit in its doctrines, even though in his day Calvin was given the nickname